PREVALENCE OF CANDIDA ASSOCIATED DENTURE STOMATITIS (CADS) AND SPECIATION OF CANDIDA AMONG COMPLETE DENTURE WEARERS OF SOUTH WEST COASTAL REGION OF KARNATAKA - Bhat, Vinaya; Sharma, S.M.; Shetty, Veena; Shastry, C.S.; Rao, Vaman; Shenoy, Shilpa M.; Saha, Santanu; Balaji, Sriram (Journal of Health and Allied Sciences NU, 2013)
A denture wearer is highly prone to develop Candida associated denture stomatitis (CADS), due to the conversion of the normal oral commensal Candida spp. into a pathogen under favorable conditions. Immuno-compromised status, trauma from the prosthesis, other systemic conditions and improper maintenance of the dentures by the patient are few of the causative agents which turn the oral balance into an unhealthy and unsuitable foundation for the wearing of the prosthesis. Prevalence of denture stomatitis caused by the fungi Candida has been identified worldwide and has been reported to be around 65 to 70% of the denture wearers. The main species that causes infection has been Candida albicans, however, recently, there is a shift to non-Candida albicans-Candida (NCAC).This cross-sectional survey was undertaken to find the prevalence of denture stomatitis and the causative species in the south westcoastal region of Karnataka.
Keywords: Candida-Associated-Denture Stomatitis; Candida species; CHROMagar; Speciation